Bone mineral density in lifelong trained male football players compared with young and elderly untrained men - Marie Hagman; Eva Wulff Helge; Therese Hornstrup; Bjørn Fristrup; Jens Jung Nielsen; Niklas Rye Jørgensen; Jesper Løvind Andersen; Jørn Wulff Helge; Peter Krustrup (Elsevier, 2018)
Purpose: The purpose of the present controlled cross-sectional study was to investigate proximal femur and whole-body bone mineral density (BMD), as well as bone turnover profile, in lifelong trained elderly male football players and young elite football players compared with untrained age-matched men. Methods: One hundred and forty healthy, non-smoking men participated in the study, including lifelong trained football players (FTE, n = 35) aged 65-80 years, elite football players (FTY, n = 35) aged 18-30 years, as well as untrained age-matched elderly (UE, n = 35) and young (UY, n = 35) men. All participants underwent a regional dual-energy X-ray Absorptiometry (DXA) scan of the proximal femur and a whole-body DXA scan to determine BMD. From a resting blood sample, the bone turnover markers (BTMs) osteocalcin, carboxy-terminal type-1 collagen crosslinks (CTX-1), procollagen type-1 amino-terminal propeptide (P1NP), and sclerostin were measured. Results: FTE had 7.3%-12.9% higher (p < 0.05) BMD of the femoral neck, wards, shaft, and total proximal femur in both legs compared to UE, and 9.3%-9.7% higher (p < 0.05) BMD in femoral trochanter in both legs compared to UY. FTY had 24.3%-37.4% higher (p < 0.001) BMD in all femoral regions and total proximal femur in both legs compared to UY. The whole-body DXA scan confirmed these results, with FTE showing similar whole-body BMD and 7.9% higher (p < 0.05) leg BMD compared to UY, and with FTY having 9.6% higher (p < 0.001) whole-body BMD and 18.2% higher (p < 0.001) leg BMD compared to UY. The plasma concentration of osteocalcin, CTX-1, and P1NP were 29%, 53%, and 52% higher (p < 0.01), respectively, in FTY compared to UY. Conclusion: BMD of the proximal femur and whole-body BMD are markedly higher in lifelong trained male football players aged 65-80 years and young elite football players aged 18-30 years compared to age-matched untrained men. Elderly football players even show higher BMD in femoral trochanter and leg BMD than untrained young despite an age difference of 47 years. Keywords: Bone mass, Bone turnover markers, Dual-energy X-ray absorptiometry, Proximal femur bone mineral density, Soccer, Whole-body bone mineral density